Tingkat Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan: Studi Empiris di Kota Pangkalpinang - Meilani Putri; Cik Marhayani; Virna Dewi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to describe the level of taxpayer compliance in paying the Rural and Urban Land and Building Tax (PBB) in Pangkalpinang City in 2024. The study employed a quantitative descriptive method with an empirical approach. A total of 81 taxpayers were selected using purposive sampling. Data were collected through questionnaires and analyzed using descriptive statistics. The results showed that the mean taxpayer compliance score was 110, which falls into the high category based on the predetermined assessment criteria. These findings indicate that taxpayers in Pangkalpinang City demonstrate a high level of compliance in fulfilling their Land and Building Tax obligations, thereby supporting the increase in Regional Original Revenue (PAD).